Ḵẖṳtbah-yi ṣadārat - Sulaimān, Shāh Muḥammad, Sir (Niẓāmī Pres, 1924)
Presidential address delivered at the Second Provincial Muslim Educational Conference of the United Provinces of Agra and Oudh (India), Budaun, 1924.